TECHNIQUES HOW TO ENHANCE VISUAL DATA ANALYSIS AND ITS DESCRIPTIONS - Khojakulova N.Kh; Khojakulova N.Kh (International Journal on Orange Technologies, 2020)
This article discusses the essential techniques in writing visual data such as graphs, process writing and map descriptions. Moreover, in this article 3 types of visual data descriptions are analyzed. Examples are also given for each type of visual data in this research work.